Critical evaluation of whole-body cryostimulation protocol in race horses - Bogard, F.; Bouchet, B.; Murer, S.; Filliard, J. R.; Beaumont, F.; Polidori, G. (Journal of Equine Veterinary Science, 2020)
Cold therapy is commonly used to relieve pain and inflammation and to aid in muscle recovery after exercise in human medicine. A number of applications have also been observed in veterinary practice. In this article, a critical evaluation of equine protocol applied with a new commercial concept of equine whole-body cryostimulation (WBC) was made. With this new concept of WBC, the protocol usually utilized for relieving pain and discomfort in humans has been extended to horses. The investigations described herein focus on the reduction of horse skin temperature when applying human WBC protocols. Based on infrared thermography measurements, results show that exposing a horse for 3 minutes to a temperature of -140°C, which are conventional parameters used for humans, does not induce sufficient skin thermal gradients in horses. Consequently, beneficial cold reflexes such as vasomotor, neuroconduction, and biochemical reactions cannot be triggered. Further investigations should therefore be carried out to design an adequate protocol specifically aimed at horses.